Time Distortions in Mind Temporal Processing in Clinical Populations - Vatakis, Argiro; Allman, Melissa (Brill, 2015)
Time Distortions in Mind brings together current research on temporal processing in clinical populations to elucidate the interdependence between perturbations in timing and disturbances in the mind and brain. For the student, the scientist, and the stepping-stone for further research. Readership: An excellent reference for the student and the scientist interested in aspects of temporal processing and abnormal psychology.